2017
DOI: 10.1016/j.redox.2016.12.023
|View full text |Cite
|
Sign up to set email alerts
|

LPS-induced renal inflammation is prevented by (−)‐epicatechin in rats

Abstract: This work investigated the capacity of (−)-epicatechin to prevent the renal damage induced by LPS administration in rats. Male Sprague Dawley rats were fed for 4 days a diet without or with supplementation with (−)-epicatechin (80 mg/kg BW/d), and subsequently i.p. injected with lipopolysaccharide (LPS). Six hours after injection, LPS-treated rats exhibited increased plasma creatinine and urea levels as indicators of impaired renal function. The renal cortex of the LPS-treated rats showed: i) increased express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 44 publications
2
40
2
Order By: Relevance
“…In addition, it should be considered that enhanced levels of ROS activate inflammatory mediators and different signalling pathways apart from the mechanisms studied in the present work (Forbes & Cooper, 2013;. In this line, it has been reported that EC is able to prevent the inflammatory response in the kidney through the downregulation of redox-sensitive pro-inflammatory pathways, such as NF-κB, NOX, TNFα, iNOS, and IL-6 (P. D. Prince, Fischerman, Toblli, Fraga, & Galleano, 2017;P. D. Prince et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…In addition, it should be considered that enhanced levels of ROS activate inflammatory mediators and different signalling pathways apart from the mechanisms studied in the present work (Forbes & Cooper, 2013;. In this line, it has been reported that EC is able to prevent the inflammatory response in the kidney through the downregulation of redox-sensitive pro-inflammatory pathways, such as NF-κB, NOX, TNFα, iNOS, and IL-6 (P. D. Prince, Fischerman, Toblli, Fraga, & Galleano, 2017;P. D. Prince et al, 2016).…”
Section: Discussionmentioning
confidence: 81%
“…This finding open the question whether MORG1 heterozygosity could play a role not only in the HIFs pathway, but as well in the NF-κB signalling path, that is activated through LPS/ TLR4 signalling. Upon LPS or TNF-α stimulation NF-kB is activated in an IKKα,β, depended manner, which phosphorylates IκB-α leading to proteasomal degradation of IκB-α and subsequent liberation, nuclear translocation and activation of the NF-κB complex [ 41 43 ]. Indeed, we were able to detect an intact NF-κB signalling path in wild-type LPS treated MORG1 +/+ mice, characterised with an increased phosphorylation levels of IκB-α and IKKα,β, as well as elevated NF-κB nuclear translocation and increased iNOS expression.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental and clinical studies, inflammatory markers such as C-reactive protein, tumor necrosis factor-alpha, interleukin 6 and nu-clear factor kappa-␤, are associated with lipids level [39]. EC has been shown to reduce chronic inflammation in various animal models and under various conditions [17,[40][41][42][43][44]. In current study, EC was found to significantly reduce IL-1beta, IL-2 and IL-6 in hyperlipidemic rats, with is in line with previous reports.…”
Section: Discussionmentioning
confidence: 99%